Prevention of deep vein thrombosis in postoperative orthopedic patients: a hybrid meta-analysis and clinical case study - Liu, Fenglan; Tan, Juan; Pan, Yulin (Frontiers in Medicine, 2025)
BackgroundDeep vein thrombosis (DVT) is a significant complication, which often comes along with orthopedic surgery, and leads risks of severe outcomes such as pulmonary embolism. Effective prevention strategies are urgently expected to promote postoperative recovery and reduce complications.ObjectiveThis study aims to measure the effectiveness of nursing interventions in preventing postoperative DVT among the patients with orthopedic surgeries, with the focus on outcomes such as DVT incidence, recovery time, and patient satisfaction. This hybrid study integrates a PRISMA-compliant meta-analysis of six independent studies with a prospective clinical case report, bridging population-level evidence and real-world nursing practice.MethodsNursing intervention details (early mobilization and patient education) were firstly collected and assessed in postoperative patients in this research. Key metrics (DVT occurrence, D-dimer level, and patient-reported outcomes) were further analyzed to determine the impact of these interventions.ResultsFollowing the nursing interventions, patients demonstrated a lower DVT incidence, the recovery rates as well as patient satisfaction were enhanced, and the symptoms of lower extremity swelling got reduced, despite challenges in adherence to the protocols.ConclusionNursing interventions play a critical role in DVT prevention in postoperative care for the patients after orthopedic surgeries. These findings support the integration of standardized nursing practices to optimize postoperative outcomes after orthopedic surgeries and highlight the need for addressing adherence barriers to maximize their effectiveness.